Automated Optimization of Capacitive Feedback Folded Cascode Amplifier Using Precomputed Lookup Tables - El Khalik, Ahmed M. Abd; Omran, Hesham (2019 7th International Japan-Africa Conference on Electronics, Communications, and Computations, (JAC-ECC), 2019)
We propose an automated optimization methodology for analog integrated circuit design. The design process is transferred to MATLAB by using precomputed lookup tables and symbolic mathematical expressions. This enables using state-of-the-art optimization algorithms in the design process without invoking the simulator in the loop. A capacitive feedback amplifier that uses a folded cascode operational transconductance amplifier (OTA) is taken as a case study to show different optimization methods and compare them. Pareto-optimal curves of power vs speed for a range of specifications are provided. Compared to Cadence Global Optimization, the proposed methodology achieves 80× shorter execution time and provides better optimization results.